Entrepreneurship Intentions Amongst South African TVET Students: An Application of the Theory of Planned Behaviour - Sundelson, Jamie (School of Management Studies, 2022)
The primary aim of the investigation was to explore the entrepreneurship intent (EI) of South African TVET students by applying the Theory of Planned Behaviour (TPB). Additional factors (demographics, community valuation, prior exposure to entrepreneurship and COVID-19 perceptions) were included as control variables within the model to assess the utility of the TPB. Student participants (N = 128) completed an online survey administered through two institutions in the Western Cape and made available by a Facebook link. The application of the TPB model scales was strongly supported by the results of the exploratory factor analyses (EFA) conducted as well as reliability analyses. Regression analyses indicated that the Theory of Planned Behaviour explained approximately 80% of the variance in entrepreneurial intention (p < .001). However, only attitudes were a significant determinant of entrepreneurial intention, whereas subjective norms and perceived behavioural control were not significant determinants of EI. Moreover, the control variables (demographic factors, community valuation, prior exposure to entrepreneurship) did not explain significant variance in EI, with the exception of COVID-19 perception, which was a significant determinant (β = .259, t = 3.159, p < .05). Hayes (2018) PROCESS macro was thereby used to investigate the moderation effect of COVID-19 perceptions, which were found to significantly moderate the relationship between perceived behavioural control and entrepreneurial intention. The contributions of the investigation are discussed and recommendations for future research are presented.